PERUMUSAN STANDAR PEMBINAAN PESERTA DIDIK: STUDI KASUS INTEGRASI PENDIDIKAN AKADEMIK DAN KARAKTER DI SDIT AL-MARHAMAH - Merri Yelliza (STKIP Subang, 2025)
This study discusses the process of formulating student development standards at SDIT Al-MARHAMAH, an Islamic-based school integrating academic education with character development. The aim of this research is to deeply explore the stages of formulating student development standards involving various school stakeholders and identify internal and external factors influencing the process. This study uses a qualitative approach with a case study design, involving in-depth interviews, participatory observation, and documentation as data collection methods. The findings reveal that the formulation of development standards at SDIT Al-MARHAMAH involves stages of needs identification, vision and mission formulation, draft preparation, and standard validation. However, key challenges include time limitations, human resources, and facility constraints, which hinder the optimal implementation of these standards. Therefore, periodic evaluation and human resource development are critical in enhancing the effectiveness of the standards' implementation. In conclusion, this research highlights the importance of internal and external collaboration and the use of technology to support the formulation and implementation of development standards that are more effective and relevant to the needs of students.